Cooperación internacional para el desarrollo en Medellín. Una mirada desde la integración en redes y formación de capital social (2019)
This article presents network bonds between organizations with the objective of making processes more dynamic through international cooperation for development. It also presents the description of certain actors and instruments of international cooperation in the city of Medellin. The content is based on the results of interviews with seventeen organizations of different types: NGOs, non-profit organizations and public and private organizations in the areas of education, health and research. The organizations studied make part of different networks to work in International Cooperation. The characteristics, legal form, members, and types of networks are described.